Advancements in the treatment of metastatic hormone-sensitive prostate cancer - Li, Hengping; Zhang, Mao; Wang, Xiangrong; Liu, Yang; Li, Xuanpeng (Frontiers in Oncology, 2022)
In the last decade, there have been substantial improvements in the outcome of the management of metastatic hormone-sensitive prostate cancer (mHSPC) following the development of several novel agents as well as by combining several therapeutic strategies. Although the overall survival (OS) of mHSPC is shown to improve with intense androgen deprivation therapy (ADT), combined with docetaxel, as well as other novel hormone therapy agents, or alongside local intervention to the primary neoplasm. Notably, luteinizing hormone-releasing hormone (LHRH) antagonists are known to cause less cardiovascular side effects compared with LHRH agonists. Thus, in this mini review we explore the different approaches in the management of mHSPC, with the aim that we may provide useful information for both basic scientists and clinicians when managing relevant clinical situations.